THE IMPACT OF PERCEIVED SERVICE QUALITY, CUSTOMER SATISFACTION ON CUSTOMER LOYALTY OF MEDINBOX - Wang, Lanyifan (Journal of Interdisciplinary Research (ISSN: 2408-1906), 2017)
The following study of this paper is to examine the impact of perceived service quality, customer satisfaction on customer loyalty of Medinbox with the 103 numbers of valid respondents. This study discusses the importance of customer Perceived Service Quality which influence Customer Overall Satisfaction, Customer Loyalty in a long-term. The results stated that Perceived Service Quality, Customer Overall Satisfaction and Customer Loyalty are significantly related to each other. Recommendations are for managers of Medinbox to understand a whole picture of how does this variable related to each other, so that they could take action into improving customer Perceived Service Quality to gain higher Customer Overall Satisfaction, in order to get Customer Trust and let customers become loyal by using service quality as a competitive advantage